The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.4049/jimmunol.173.5.2995
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mutation in CD83 Results in the Development of a Unique Population of CD4+ T Cells

Abstract: Using a mouse mutagenesis screen, we have identified CD83 as being critical for the development of CD4+ T cells and for their function postactivation. CD11c+ dendritic cells develop and function normally in mice with a mutated CD83 gene but CD4+ T cell development is substantially reduced. Additionally, we now show that those CD4+ cells that develop in a CD83 mutant animal fail to respond normally following allogeneic stimulation. This is at least in part due to an altered cytokine expression pattern character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
74
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 21 publications
7
74
0
Order By: Relevance
“…1B), suggesting that CD83 does not participate in the function of CD8 ϩ T cells. Similar observations as published for CD83 Ϫ/Ϫ mice were described for CD83 mutant mice (17). The engineered genetic disruption of CD83 also impaired the development of CD4 ϩ T cells, while the CD8 ϩ single-positive thymocyte development and numbers were normal (17).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…1B), suggesting that CD83 does not participate in the function of CD8 ϩ T cells. Similar observations as published for CD83 Ϫ/Ϫ mice were described for CD83 mutant mice (17). The engineered genetic disruption of CD83 also impaired the development of CD4 ϩ T cells, while the CD8 ϩ single-positive thymocyte development and numbers were normal (17).…”
Section: Discussionsupporting
confidence: 83%
“…Similar observations as published for CD83 Ϫ/Ϫ mice were described for CD83 mutant mice (17). The engineered genetic disruption of CD83 also impaired the development of CD4 ϩ T cells, while the CD8 ϩ single-positive thymocyte development and numbers were normal (17). This defect in CD4 ϩ T cell development results from modifications of the thymic environment as CD83 Ϫ/Ϫ thymocytes and stem cells developed normally within WT mice (16), suggesting that CD83 expression on thymic epithelial cells contributes to CD4 ϩ but not CD8 ϩ T cell development within the thymus.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…CD8 ϩ T cells in lupusprone mice are impaired in expansion, acquisition of memory, secretion of cytokine, and suppression of autoimmunity (8,82) and because CD83 appears to have a role in CD8 ϩ function, it is possible that down-regulation of the former could contribute to abnormal CD8 ϩ function in SLE. In addition, CD4 ϩ T cells that develop in a CD83 mutant animal fail to respond normally following allogeneic stimulation (83), at least in part due to an altered cytokine expression pattern characterized by an increased production of IL-4 and IL-10 and diminished IL-2 production, findings typically seen in SLE. Thus, absence or decrease of CD83 in SLE DCs may result in the generation of T cells with an altered activation and cytokine profile.…”
Section: Discussionmentioning
confidence: 99%
“…Among these molecules is CD83, first described by Zhou et al (4), CD83 is one of the most useful markers for identifying mature DCs capable of activating naïve T cells (5-8). CD83 expression also occurs on certain T cell subsets (9, 10), B cells (10-12), and murine thymic epithelial cells (13,14). Studies of CD83 transcription have shown that it is mediated by NF-B during the induction of adaptive responses (15,16).…”
mentioning
confidence: 99%